2010
DOI: 10.1161/atvbaha.109.196022
|View full text |Cite
|
Sign up to set email alerts
|

Postmenopausal Hormone Therapy and Risk of Idiopathic Venous Thromboembolism

Abstract: Objective-Oral estrogen therapy increases venous thromboembolism risk among postmenopausal women. Although recent data showed transdermal estrogens may be safe with respect to thrombotic risk, the impact of the route of estrogen administration and concomitant progestogens is not fully established. Methods and Results-We used data from the E3N French prospective cohort of women born between 1925 and 1950 and biennially followed by questionnaires from 1990. Study population consisted of 80 308 postmenopausal wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
128
1
15

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 238 publications
(148 citation statements)
references
References 47 publications
4
128
1
15
Order By: Relevance
“…27 Hepatobiliary effects of pro gestagens have been explored to a lesser extent than those of estrogens. 26 The E3N cohort study has assessed the impact of menopausal hormone therapy on several outcomes, including breast cancer, 17,28 diabetes onset, 29 thromboembolic events 30 and asthma. 31 Unlike most reports from cohort studies in which exposure to menopausal hormone therapy is assessed only at baseline, data on the use of menopausal hormone therapy and covariates in the E3N cohort were updated every 2 years during the follow-up period.…”
Section: Researchmentioning
confidence: 99%
“…27 Hepatobiliary effects of pro gestagens have been explored to a lesser extent than those of estrogens. 26 The E3N cohort study has assessed the impact of menopausal hormone therapy on several outcomes, including breast cancer, 17,28 diabetes onset, 29 thromboembolic events 30 and asthma. 31 Unlike most reports from cohort studies in which exposure to menopausal hormone therapy is assessed only at baseline, data on the use of menopausal hormone therapy and covariates in the E3N cohort were updated every 2 years during the follow-up period.…”
Section: Researchmentioning
confidence: 99%
“…Drug carriers enhance the physicochemical properties of drugs, facilitate the penetration of drug molecules into the skin, and improve skin permeation by skin hydration and interaction with skin lipids [32]. Case-control studies have shown a lower risk of venous thromboembolism (VTE) with transdermal estrogen therapy than with the oral administration of estrogen [33]. This finding was confirmed by a cohort study in which transdermal estrogens and the risk of VTE recurrence were not correlated [34].…”
Section: Discussionmentioning
confidence: 99%
“…W trzech dużych badaniach obserwacyjnych: Estrogen and THromboEmbolism Risk (ESTHER) [5], Etude Epidemiologique de Femmes de la Mutuelle Générale de l'Education Nationale (E3N) [9], UK General Practice Research Database (GPRD) [10] stwierdzono, że w trakcie stosowania MHT drogą przezskórną ryzyko wystąpienia ŻChZZ nie wzrasta. Względne ryzyko powikłań zakrzepowo-zatorowych wynosi 1,2 (95% CI 0,9-1,7) na podstawie metaanalizy 7 badań kliniczno-kontrolnych i 1 pracy kohortowej.…”
Section: żYlna Choroba Zakrzepowo-zatorowaunclassified